Essays in corporate finance - Im, H (2012)
This thesis contributes to the empirical literature on how firms meet exceptional financing needs in relation to “investment spikes” or years with unusually large investment activities. In the earlier part of the thesis, I show that the financing of investment during an investment spike is very different from that at other times. I have done this using data for publicly traded US firms over the period 1988 to 2007 and a filtering procedure suggested by Bond et al. (2006). Specifically, external finance, in particular debt finance, is very important in financing investment in years categorized as investment spikes, confirming the findings of Mayer and Sussman (2005). In addition, it has been found that firms with smaller size, lower profitability, more future growth opportunities, fewer tangible assets and more R&D; spending tend to use more equity finance in relation to large investment requirements. I also propose the use of the Markov-switching filter to identify investment spikes. In implementing the Markov-switching filter, I apply a first-order two-state Markov-switching mean model to the investment rates de-trended using Hodrick and Prescott's (1997) filter. A Gibbs-sampling procedure is used to produce the marginal posterior distributions of unobserved state variables and model parameters. Among other advantages, this filter allows us to identify multi-year investment spikes. I show that two-year investment spikes identified by the Markov-switching filter are financed quite similarly to single-year investment spikes and that main findings are robust to calendar-time-dependent clustering of investment spikes generated by macroeconomic shocks. In the later part of the thesis, I find there is a positive effect of share liquidity on the propensity to raise debt finance. Using a sample of firm-year observations identified as investment spikes, I find that firms with more liquid shares tend to rely more heavily on debt to finance investment spikes. This result is robust to a control for the effects of firm size and other firm characteristics, the use of various leverage measures, and the use of a whole sample with investment spike characteristics. Another important finding is that firms with more liquid shares tend to have higher target leverage ratios. One interpretation of these results is that information spillovers from the presence of more informative share prices allow firms with more liquid shares to borrow on more favourable terms in normal times, as well as to obtain additional debt finance at lower costs when taking advantage of unusually large investment opportunities.